2016
DOI: 10.1002/qua.25230
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of metal‐free organic dyes based on different configurations for efficient dye‐sensitized solar cells

Abstract: Considering different solar dyes configuration, four novel metal‐free organic dyes based on phenoxazine as electron donor, thiophene and cyanovinylene linkers as the π‐conjugation bridge and cyanoacrylic acid as electron acceptor were designed to optimize open circuit voltage and short circuit current parameters and theoretically inspected. Density functional theory and time‐dependent density functional theory calculations were used to study frontier molecular orbital energy states of the dyes and their optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The excited state must be at a more negative potential, on an electrochemical scale, than the TiO 2 CB edge for an efficient injection of electrons from the LUMO level of dyes into the CB of TiO 2 . Conversely, the HOMO level of dyes must be more positive than the redox potential of the electrolyte for the regeneration of the oxidized dye . To evaluate the feasibility of electron injection from the LUMO level of dyes into the CB of TiO 2 and regeneration of oxidized dyes by the redox mediator, CV was performed to measure the oxidation potential of the new sensitizers in CH 2 Cl 2 containing tetra‐ n ‐butylammonium hexafluorophosphate (TBAPF 6 ; 0.1 m , Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excited state must be at a more negative potential, on an electrochemical scale, than the TiO 2 CB edge for an efficient injection of electrons from the LUMO level of dyes into the CB of TiO 2 . Conversely, the HOMO level of dyes must be more positive than the redox potential of the electrolyte for the regeneration of the oxidized dye . To evaluate the feasibility of electron injection from the LUMO level of dyes into the CB of TiO 2 and regeneration of oxidized dyes by the redox mediator, CV was performed to measure the oxidation potential of the new sensitizers in CH 2 Cl 2 containing tetra‐ n ‐butylammonium hexafluorophosphate (TBAPF 6 ; 0.1 m , Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…For the efficient operation of sensitizers in DSCs, the excitedstate potentiala nd the oxidation potentialo ft he sensitizers must match the conduction band (CB) of the TiO 2 electrode and the redox potential of the electrolyte, respectively.T he excited state must be at am ore negative potential, on an electrochemical scale, than the TiO 2 CB edge for an efficient injection of electrons from the LUMO level of dyes into the CB of TiO 2 .C onversely,t he HOMO level of dyes must be more positive than the redox potentialo ft he electrolyte fort he regeneration of the oxidized dye. [28,29] To evaluate the feasibility of electron injection from the LUMO level of dyes into the CB of TiO 2 and regenerationo fo xidized dyes by the redox mediator, CV was performed to measure the oxidation potential of the new sensitizers in CH 2 Cl 2 containing tetra-n-butylammonium hexafluorophosphate( TBAPF 6 ;0 .1 m,F igure 3a). In addition, we measured the cyclic voltammograms (CVs) of L156 and L224 adsorbed on TiO 2 (Figure 3a,i nset) in acetonitrile to obtain am ore realistic estimation of the driving force for dye regeneration by the electrolyte redox mediator.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Ferdowsi et al . 32 studied the frontier molecular orbital (FMO) energy and optical absorption of four novel organic dyes containing phenoxazine as electron donor, thiophene and cyanovinylene linkers as the π -bridge, which indicated that D2–4 dyes could be suitable candidates as sensitizers. Feng et al .…”
Section: Introductionmentioning
confidence: 99%
“…Density functional methods have emerged as promising and reliable tools for obtaining desirable results of dye sensitizers in DSSCs . These methods allow for the optimization of DSSC dyes in terms of either change in the structure or physical properties like, temperature, solvents, external field etc..…”
Section: Introductionmentioning
confidence: 99%
“…[39,44,45] Density functional methods have emerged as promising and reliable tools for obtaining desirable results of dye sensitizers in DSSCs. [46][47][48][49][50][51][52][53][54] These methods allow for the optimization of DSSC dyes in terms of either change in the structure or physical properties like, temperature, solvents, external field etc.. Effective and accurate quantum mechanical modeling of the ground sate as well as excited state properties can help in predicting electronic as well as spectroscopic characteristics of the dye sensitizers.…”
Section: Introductionmentioning
confidence: 99%